Mortalidade por câncer de mama nas mulheres brasileiras no período de 1980 a 2009 - GONZAGA, Carolina Maciel Reis (2011)
Introduction: Breast cancer is the principal cause of death from cancer in women in Brazil and worldwide. Brazil has important social differences, therefore, to understand the mortality rates for female breast cancer, it is necessary to look at the issue of spatial inequalities in income and opportunities characteristic of Brazilian society. Aim: To describe the temporal evolution of breast cancer mortality in Brazil, in its macro-regions and Federal States from 1980 to 2009. Materials and Methods: Ecological time series, using data on deaths from breast cancer registered in the Mortality Information System (SIM/MOH) and the data of population census by the Brazilian Institute of Geography and Statistics (IBGE). Mortality trends analysis was performed using Poisson s regression model. Results: for Brazil it was observed a 0.4% stabilization trend in women breast cancer mortality since 1994 (95% CI -01 0.8; p = 0.08). Southeast regions showed decreasing trends -0.9% (95% CI -1.6 -0.2; p = 0.01), in South it was observed a -0.3% stabilization (95% CI -1.0 0.3; p = 0.31), whereas the Northeast region stands out with a higher 5.3% increasing trends per year (95% CI 3.9 6.7; p <0.01). A significant decreasing mortality trend was observed in São Paulo -1.9% (95% CI -2.9 -0.9; p < 0.01), Rio Grande do Sul -0.8% (95% CI -1.4 -0.1; p = 0.03) and Rio de Janeiro -0.6% (95% CI -1.1 -0.1; p = 0.03). The highest increases in mortality trends were observed in Maranhao 12% (95% CI 2.5 22.3; p < 0.01), Paraiba 11.9% (95% CI 7.3 16.7; p <0.01) and Piaui 10.9% (95% CI 6.3 15.7; p <0.01). Conclusion: Brazil presented a stabilization trend regarding women breast cancer mortality rates, however, when regions and Federal States were analyzed, mortality rates presented unequal, with decreasing trends and stabilization in zone with higher socioeconomic level and higher increasing trends among zone with lower socioeconomic level.